A phase-field-crystal alloy model for late-stage solidification studies involving the interaction of solid, liquid and gas phases. (8th January 2018) - Wang, Nan; Kocher, Gabriel; Provatas, Nikolas
Abstract : We present a multiphase binary alloy phase-field-crystal model. By introducing density difference between solid and liquid into a previous alloy model, this new fusion leads to a practical tool that can be used to investigate formation of defects in late-stage alloy solidification. It is shown that this model can qualitatively capture the liquid pressure drop due to solidification shrinkage in confined geometry. With an inherited gas phase from a previous multiphase model, cavitation of liquid from shrinkage-induced pressure is also included in this framework. As a unique model that has both solute concentration and pressure-induced liquid cavitation, it also captures a modified Scheil–Gulliver-type segregation behaviour due to cavitation. Simulation of inter-dendritic channel solidification using this model demonstrates a strong cooling rate dependence of the resulting microstructure. This article is part of the theme issue 'From atomistic interfaces to dendritic patterns'.